1999
DOI: 10.1093/hmg/8.13.2497
|View full text |Cite
|
Sign up to set email alerts
|

The Human Magel2 Gene and Its Mouse Homologue Are Paternally Expressed and Mapped to the Prader-Willi Region

Abstract: Prader-Willi syndrome (PWS) is a complex neurogenetic disorder. The phenotype is likely to be a contiguous gene syndrome involving genes which are paternally expressed only, located in the human 15q11-q13 region. Four mouse models of PWS have been reported but these do not definitively allow the delineation of the critical region and the associated genes involved in the aetiology of PWS. Moreover, targeted mutagenesis of mouse homologues of the human candidate PWS genes does not appear to result in any of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 29 publications
3
94
0
1
Order By: Relevance
“…Peg3 (Kaneko-Ishino et al 1995) is known to be imprinted in the human placenta (Hiby et al 2001); however, the imprinting status in the mouse placenta had not been reported. Ndn (MacDonald and Wevrick 1997) and Magel2 (Boccaccio et al 1999) are both expressed in the mouse placenta, whereas the imprinting status was not clear. Rian (Hatada et al 2001), Zim1 (Kim et al 1999), Meg3 (Miyoshi et al 2000), Mirg (Seitz et al 2004), Usp29 (Kim et al 2000), Impact (Hagiwara et al 1997), Nnat (Kagitani et al 1997), Zdbf2 (Kobayashi et al 2009), and Zrsr1 (Hatada et al 1993) were not previously reported to be imprinted in the mouse placenta either.…”
Section: Detection Of Significant Parent-of-origin Effectsmentioning
confidence: 99%
“…Peg3 (Kaneko-Ishino et al 1995) is known to be imprinted in the human placenta (Hiby et al 2001); however, the imprinting status in the mouse placenta had not been reported. Ndn (MacDonald and Wevrick 1997) and Magel2 (Boccaccio et al 1999) are both expressed in the mouse placenta, whereas the imprinting status was not clear. Rian (Hatada et al 2001), Zim1 (Kim et al 1999), Meg3 (Miyoshi et al 2000), Mirg (Seitz et al 2004), Usp29 (Kim et al 2000), Impact (Hagiwara et al 1997), Nnat (Kagitani et al 1997), Zdbf2 (Kobayashi et al 2009), and Zrsr1 (Hatada et al 1993) were not previously reported to be imprinted in the mouse placenta either.…”
Section: Detection Of Significant Parent-of-origin Effectsmentioning
confidence: 99%
“…There have been no reports of its expression in mammalian embryos. MAGE-like 2 (Magel2) has been mapped to the Prader-Willi syndrome (PWS) region and is imprinted in the mouse, cow and human, with paternal expression only in the adult brain of both the mouse and human (Boccaccio et al 1999;Khatib et al 2007). Makorin, ring finger protein, 3 (Mkrn3/Znf127) is paternally expressed in both the mouse and human and is predicted to function as a ribonucleoprotein (Jong et al 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of necdin in mouse development mirrors the cultured cell system, because necdin is expressed in many but not all postdifferentiation stage neurons. necdin is a member of the MAGE (melanoma antigen-encoding gene)/necdin gene family that also includes MAGEL2, also deficient in PWS (Boccaccio et al, 1999;Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%